An Analysis of the Activities of Daily Living (ADL) among Aged People in Rural Areas of Western Odisha, India - Nath, Nibedita; Minz, Sarojini; Mohapatra, Monalisa (Indian Journal of Community Health, 2023)
Background: A decline in fertility rate and expansion in life span has resulted in the growth in the percentage of aged populations in the whole world. India and Odisha are no exceptions. Objectives: The objective of the present paper is to find out the incidence of functional ability/inability among the aged people of the rural areas of western Odisha of India. Materials and Methods: Katz Scale of ADL was used to assess the functional ability of elderly people. Six activities of daily living such as (Bathing, Dressing, Toilet, Mobility, Continence, and Feeding) were analyzed as per age and sex of the samples. Results: Of all the samples (1992), 98.5 percent are physically independent and only 1.4 percent are physically dependent. Out of 945 female elderly people, 931 (98.1%) are independent and out of 1047 male elderly people 1033 (98.6%) are independent. The physical dependency of females is more with a ?2 – value of 0.075 and p – value of 0.466. The age group wise ?2 – value is 20.899 (3) and p – value of 0.001. Conclusion: Lesser physical dependency is found among the elderly people in rural areas. An increase in dependency is seen with the increase in age.